2017
DOI: 10.1016/j.tra.2017.02.007
|View full text |Cite
|
Sign up to set email alerts
|

Testing for inertia effect when a new tram is implemented

Abstract: This work is licensed under a Creative Commons Attribution-NonCommercial-NoDerivatives 4.0 International licence Newcastle University ePrints -eprint.ncl.ac.uk

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
21
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(29 citation statements)
references
References 31 publications
8
21
0
Order By: Relevance
“…Other relevant research includes studies of the impact of inertia on adopting the new alternative which requires a combination of revealed-preference (RP) and stated-preference (SP) data or launching SP surveys twice, i.e. before and after the implementation of the novel facility/ service (González et al, 2017;Jensen et al, 2013). It has also been suggested that intrinsic personal preference might be a driving factor of choosing a specific alternative (International Air Transport Association, 2003), and that habit could act as a barrier to the change in mode choice bahviour and breaking old habits can potentially result in mode shift (Blainey et al, 2012;Thøgersen, 2006).…”
Section: Variety-seeking Analysismentioning
confidence: 99%
“…Other relevant research includes studies of the impact of inertia on adopting the new alternative which requires a combination of revealed-preference (RP) and stated-preference (SP) data or launching SP surveys twice, i.e. before and after the implementation of the novel facility/ service (González et al, 2017;Jensen et al, 2013). It has also been suggested that intrinsic personal preference might be a driving factor of choosing a specific alternative (International Air Transport Association, 2003), and that habit could act as a barrier to the change in mode choice bahviour and breaking old habits can potentially result in mode shift (Blainey et al, 2012;Thøgersen, 2006).…”
Section: Variety-seeking Analysismentioning
confidence: 99%
“…Cantillo et al (2007) developed inertia models, which were later extended by Yáñez et al (2010). Similarly, González et al (2017) analysed positive and negative inertia in mode choice with revealed preference (RP) and stated preference (SP) data, based on a mixed logit model formulation. Cherchi et al (2013) used hybrid choice models to represent inertia by measuring the tendency to stick with the same alternative (inertia) via lagged variables.…”
Section: Introductionmentioning
confidence: 99%
“…A more complex formulation is needed to consider the effects of the direct social interaction by comparing the responses between the experiments SP1 and SP2. For this specific purpose, we adapt the methodology used to take into consideration the presence of inertia/habit (or propensity to change if inertia is negative) presented in previous travel behaviour research (Cantillo et al, 2007;Cherchi & Manca, 2011;González et al, 2017). As described in these studies, the inertia is the effect of "previous valuation of alternatives" on the present choice.…”
Section: Social Influence and Specification Of The Social Interaction Variablementioning
confidence: 99%